Revisiting Liberal Democracy and Asian Values in Contemporary Indonesia - Muhammad Bahrul Ulum; Nilna Aliyan Hamida (The Constitutional Court of the Republic of Indonesia, 2018)
This paper aims to examine the complex and often contentious relationship between constitutionalism and integralism in the Indonesian government and provides a criticism of democratization within the contemporary state. Integralist state portrays the relationship between the state and the people as analogous to a family, with the state as a father and the people as children (the Family Principle). Those that adhere to this view, with regard to contemporary Asian politics, claim that Asian values are inherently integralist, that Asia’s particular history and values different considerably from the West’s, and that Pancasila, Indonesia’s state philosophy, is utilized to establish romanticized relations between the ruler and the ruled. The data presented in this paper was collected from relevant articles on Indonesian democracy and Asian values. It also demonstrates how Pancasila, as Indonesia’s core guiding philosophy, has influenced debates over how the constitutional should be applied and interpreted. As the research shows, during the regimes of Sukarno and Suharto, Pancasila was manipulated in order to promote the goals of the state, and that a reliance on integralism during Indonesia’s founding years severely diminished human rights and Indonesia’s capacity for an efficient democracy. By continually putting the priorities of the state above those of the people, the Indonesian government has contradicted its adoption of human rights and liberal democracy is often challenged by the spirit of integralism.